A proposed graphical electrical signatures supervision method to study PV module failures. (June 2015) - El Basri, Y.; Bressan, M.; Seguier, L.; Alawadhi, H.; Alonso, C.
Highlights: We developed a new method to detect electrical signatures failures on I – V curves. We elaborated PV monitoring system which measures I – V characteristic on six PV modules. We analyzed all deviations on I – V curves under the influence of numerous failures such as shadow effect and oxidation. Abstract: The current literature has an important lack of knowledge on the various types of failures in terrestrial PV systems. This works seeks to remedy this issue by proposing a new method to detect failures based on simple electrical measurements. This helps to maximize the PV power production and to improve the knowledge of the environmental impact on premature failures. To validate this approach, this work proposes the analysis of numerous I – V curves under failure conditions. These curves are reproduced experimentally on a PV central, validating the proposed method.